Family Patriarchy and Self-Reliant Development among Students in Akwa Ibom State, Nigeria (Global Journal of Human-Social Science, 2017)
The study determined the relationship between family patriarchy and self-reliance of students in Secondary Schools in Akwa Ibom State Nigeria Research questions and hypotheses were formulated for a research direction The study adopted a correlational research design Stratified random sampling technique was used The researchers developed instrument called Family-Patriarchy for Self-reliance Scale FPSRS with a reliability coefficient of 71 and 82 on Cronbach Alpha were used to elicit data from 400 respondents which 380 was suitable for data analyses respondents were randomly selected from the population of 58 230 students Linear Regression statistics was used for the data analyses The research questions were answered with Pearson r statistics while the hypotheses were tested using t-test of significance of correlation Findings indicated very high moderate positive significant relationships among variables The study concluded that family patriarchy is significantly to build self-reliant traits It was recommended that parents should rear their children to foster the self-reliant spirit in males and females to ensure equal opportunities for self-reliance
Keywords: family; parental patriarchy; heterosexual patriarchy